Quality of baked Pan de Sal as affected by dough freezing rate - Salvador, Nina D.
Effects of freezing of dough on the quality of baked pan de sal were determined. Molded and scaled pan de sal dough was frozen using two methods, slow freezing using an upright freezer and rapid freezing using an air blast freezer. The frozen doughs were stored in an upright freezer with a temperature of -20±2°C until signs of deterioration were evident. Unfrozen dough was baked and analyzed to serve as control. Manifestation damage was observed after four weeks frozen storage. Slow freezing resulted in greater inhibition of yeast activity and deterioration of gluten properties and baking quality of pan de sal dough compared with rapid freezing. Slow freezing caused a higher degree of cellular and structural damage, resulting in weakened gluten network, dehydrated dough, less viable yeast cells and accelerated staling of the baked product.